Steamed Mini Brownies with Sweet Potatoes: A Processed Food Business Innovation to Support Local Food Conservation - Juwaria Muqtadir (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to develop a business plan for processed foods made from local tubers as a strategy for local food conservation, and to evaluate the success of the promotion through the implementation of the Mini Steamed Tuber Brownies business. The study also aims to assess consumer acceptance and the economic feasibility of the business as a basis for sustainable business development. Methodology: Descriptive and action research methods were applied through semi-structured interviews, questionnaire surveys, strengths, weaknesses, opportunities, and threats analysis, break-even analysis, benefit-cost ratio analysis, and nonparametric statistical tests. Data processing used Microsoft Excel and SPSS. Research instruments included interview guidelines, observation sheets, promotional media, and respondent questionnaires. Main Findings: The Steamed Tuber Mini Brownies product is suitable for consumption, production, and marketing. Promotional strategies are a key factor in increasing consumer acceptance. Female consumers and employees demonstrated higher levels of acceptance than other groups. Order-based sales yielded greater profits than individual sales. Economic analysis indicates that the business is feasible to continue, although it requires increased production efficiency and a strengthened marketing strategy. Novelty/Originality of this study: The novelty of this research lies in the integration of local tuber conservation with the development and implementation of a home-based processed food business plan. This study not only assesses product potential but also directly measures promotional success and business feasibility, thus providing a practical model for local food development oriented toward conservation and economic sustainability.